Vibration radiation from buried plastic water pipes: An experimental investigation at the ground surface - Muggleton, J. M.; Brennan, M. J. [UNESP]; Gao, Y. (My University, 2012)
'Mapping the Underworld' is a research initiative that is seeking to address the consequences arising from an inability to consistently locate the buried utility service infrastructure without resorting to extensive excavations. It primarily focuses on developing a prototype multi-sensor platform that can be used to improve the probability of detecting all buried utilities below the ground surface. One of the four technologies to be incorporated in the device is low-frequency vibro-acoustics, and techniques for detecting buried infrastructure, in particular plastic water distribution pipes, are being investigated. The technique reported on here involves excitation of the pipe at some known location with concurrent vibrational mapping of the ground surface. Measurements have been made on both a dedicated pipe rig and a live test main; the relationships between the excitation of a pipe at the surface, the wave propagation along the pipe and its contained fluid, and the subsequent radiation up to the ground surface are explored. © (2012) by the Katholieke Universiteit Leuven Department of Mechanical Engineering All rights reserved.